Boosting GDP through Technology: Exploring the Impact of Digital Inclusion in Indonesia - Moch Rifqi Rizal; Hidayatullah, Firda (Yayasan Sinergi Kawula Muda, 2024)
This research examines the influence of digital inclusion on Indonesia's GDP growth from 2017 to 2022. The study utilizes quantitative panel data analysis, enabling an in-depth investigation of the impact of mobile phone ownership and internet access on GDP, using data sourced from the Indonesian Central Bureau of Statistics (BPS) and other sources. The findings reveal that increased mobile phone ownership significantly enhances GDP, underscoring the role of communication technology in driving economic growth. However, while internet access is essential, it does not demonstrate a significant impact on GDP during the studied period, indicating areas for potential improvement in infrastructure and digital literacy.